Kinematics and Dynamics Analysis of a Two-degree-of-freedom Arm Rehabilitation Robot - Xin Meng; Tao Qin; Fuquan Tu (Jixie chuandong)
A two-degree-of-freedom arm rehabilitation robot with two-link series structure is designed for the requirements of upper limb rehabilitation training. Firstly, the forward and inverse kinematics of the robot is analyzed based on D-H method. The forward and inverse kinematics theory model and mechanism model of the robot are established and analyzed by using Matlab/Simulink and SimMechanics toolbox. The analysis results verify the correctness of robot kinematics modeling. According to the ergonomics related standards and the arm joints range requirements, a co-simulation model of the robot and arm mechanism is established to determine the workspace of robot. The trajectory planning of the robot for drawing circle training is completed, which laid the foundation for robot motion control. Finally, the dynamics model of the robot is established based on the simultaneous constraint method, the driving torque of each joint is determined, a basis for the selection of driving motors and controller parameters is provided.